Burst intensification by singularity emitting radiation in multi-stream flows. Issue 1 (December 2017) - Pirozhkov, A.; Esirkepov, T.; Pikuz, T.; Faenov, A.; Ogura, K.; Hayashi, Y.; Kotaki, H.; Ragozin, E.; Neely, D.; Kiriyama, H.; Koga, J.; Fukuda, Y.; et al.
Abstract Burst Intensification by Singularity Emitting Radiation (BISER) is proposed. Singularities in multi-stream flows of emitting media cause constructive interference of emitted travelling waves, forming extremely localized sources of bright coherent emission. Here we for the first time demonstrate this extreme localization of BISER by direct observation of nano-scale coherent x-ray sources in a laser plasma. The energy emitted into the spectral range from 60 to 100 eV is up to 100 nJ, corresponding to 1010 photons. Simulations reveal that these sources emit trains of attosecond x-ray pulses. Our findings establish a new class of bright laboratory sources of electromagnetic radiation. Furthermore, being applicable to travelling waves of any nature (e.g. electromagnetic, gravitational or acoustic), BISER provides a novel framework for creating new emitters and for interpreting observations in many fields of science.